New species and records of Tullbergiidae (Collembola, Poduromorpha) from Xinjiang province, Northwest China - Gao, Yan; Bu, Yun (Zootaxa, 2022)
The Tullbergiidae of Xinjiang Province, Northwest China were studied from this region for the first time. Six species belonging to four genera are identified from 260 specimens. A new species Multivesicula zhengi sp. nov. is described and illustrated, two new Chinese records Wankeliella intermedia Potapov & Stebaeva, 1997 and Mesaphorura critica Ellis, 1976 are redescribed and photographed based on new materials. In addition, Mesaphorura pacifica Rusek, 1976, Mesaphorura yosii (Rusek, 1967) and Paratullbergia qilianensis Bu & Gao, 2019 are also recorded in Xinjiang for the first time. Multivesicula zhengi sp. nov. is characterized by the pseudocelli formula as 11/122/11111, seta px on Abd. IV is present, and sensillum p3 on Abd. V is weakly differentiated. The new species can be distinguished from all congeners by the body chaetotaxy and the pseudocellus formula.